Sistem Pendukung Keputusan Karyawan Terbaik Menggunakan Metode Weight Product (WP) (Studi Kasus : Universitas Pasir Pengaraian) - Dona .; Kiki Yasdomi; Urfi Utami (RJOCS (Riau Journal of Computer Science), 2018)
Weighted Product is one of the methods used in solving the problem of FADM (Fuzzy Multi Attribute Decision Making). Weighted Product requires a normalization process because it multiplies the assessment results of each attribute, the multiplication product has not been meaningful if it has not been compared with the standard value. The weights for attributes serve as positive ranks in the multiplication process, while the cost weight serves as a negative rank. The steps taken in the process of Weighted Product method is by using multiplication for each criteria match rating and rating the each criterion with the weight of the criteria. This method is used to find the best alternative of the many alternatives that exist with the best weight. From the completion of this thesis the authors do research by how to choose the best employees at the University of Pasir Pengaraian according to predetermined criteria.